Trident K9 warriors [compact disc, unabridged] : my tales from the training ground to the battlefield with elite Navy SEAL canines - Ritland, Mike (Macmillan Audio, 2013)
Former Navy SEAL Mike Ritland, after retiring from the military, started a company to provide a special service to SEAL teams: training and supplying dogs for SEAL combat missions. Now, listeners will learn more about these spectacular dogs who are much like the soldiers they work beside: fiercely aggressive and athletic, devoted to duty, and tough despite pain, injury, or fear. Ritland explains how the dogs are trained, the missions they undertake, and the character traits required to serve.